THE ROLE OF ENVIRONMENTAL, SOCIAL, GOVERNANCE AND FIRM SIZE IN ENHANCING FIRM VALUE - Rofiq, Abdul; Sunarto, Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) dimensions, as well as firm size, on firm value as measured by Tobin’s Q ratio. ESG has become an increasingly central focus in modern business practices in response to sustainability demands and stakeholder expectations, although previous empirical findings have shown inconsistent effects of ESG and firm size on firm value. This research employs a quantitative approach using secondary data from 69 companies in the mining, food, and beverage sectors listed on the Indonesia Stock Exchange (IDX) during 2023–2024. ESG scores were obtained from the Katadata ESG Index, while financial data were sourced from companies’ annual reports. Data analysis was conducted using multiple linear regression. The results show that the Governance variable has a positive effect on firm value at a 10% significance level, and Firm Size has a significant positive effect at a 5% significance level, whereas the Environmental and Social variables do not show significant effects. These findings indicate that good corporate governance and larger firm scale are important factors influencing market perceptions of firm value.